ECOLOGICAL VALUE OF KECAP PAMALI IN THE COMMUNITY OF KAMPUNG NAGA, TASIKMALAYA REGENCY - Asep Deni Gustiana; Mamat Supriatna (Pusat Penerbitan Universitas (P2U) Unisba, 2021)
People currently live in a modern and technological era, as a result, the local wisdom of an area is starting to erode. Even though there are many values contained in local wisdom that can be adopted and applied in an educational process. This article aims to describe comprehensively the results of the analysis of pamali soy sauce in the perspective of the people of Kampung Naga. In addition, this article discusses the ecological value contained in kecap pamali and the possibility of its culture in elementary school education. The method used is literature review and field study in the form of interviews and observations. The observations were made to see the behavior of the people of Kampung Naga related to kecap pamali.